Chronic High Intensity Interval Training (HIIT) exercise in adolescent rats results in cocaine place aversion and ΔFosB induction - Nikki Hammond; Nabeel Rahman; Sam Zhan; Mark S. Gold; Kenneth Blum; Teresa Quattrin; Yun Young Yim; Eric J. Nestler; Panayotis K. Thanos (PLoS ONE, 2025)
High-Intensity Interval Training (HIIT) is a form of exercise that has been greatly popularized over the past few years for its many health benefits. Similar to other forms of exercise, HIIT may be beneficial in the prevention of substance use behaviors; however, the extent to which HIIT can impact the reinforcing effects of drugs of abuse during adolescence has not been fully evaluated. Here, we assess the effects of HIIT during adolescence on subsequent cocaine conditioned place preference (CPP) in male Lewis rats. The HIIT exercise exposed rats ran on a treadmill for 30 minutes daily (ten three-minute cycles) for six weeks with progressive speed-increased up to 0.8 mph (21.5m/min), while the sedentary rats remained in their home cage. Following the six weeks of exercise, rats were tested for cocaine (25 mg/kg) CPP. Following completion of the behavior test ∆FosB levels were measured in the brain. Results showed that the HIIT rats showed significantly attenuated place preference (−19%) in their time spent in the cocaine-paired chamber compared to the sedentary environment rats. In addition, HIIT rats had significantly higher (65%) striatum ∆FosB levels compared to the sedentary rats. Our findings show that HIIT exercise during adolescence could be protective against cocaine abuse which may be mediated by an increase in ∆FosB. This finding has important clinical implications with respect to exercise mediated protection against substance misuse and abuse. Future studies will examine this effect in females as well as the potential underlying mechanisms.